Strategi Inovasi Startup Digital: Analisis Model Bisnis Agile, Pendekatan Lean, dan Akses Permodalan di Era Ketidakpastian - Aziza Regieta Adzani; Shapna Rahma Dhani; Siti Syarah Rahmawati; Ida Farida Adi Prawira (CV. ITTC INDONESIA, 2026)
Digital transformation offers both innovation prospects and significant uncertainty for entrepreneurs. This article examines the strategic integration of adaptive business models, efficient operational methodologies, and capital access within the digital entrepreneurship ecosystem. Findings indicate that startup success relies heavily on the implementation of the Digital Entrepreneurship Ecosystem Model (DEEM) and agile business model innovation prioritizing experimentation and market validation. The application of the Lean Startup method through the Minimum Viable Product (MVP) has proven effective in mitigating business failure risks. Furthermore, Artificial Intelligence (AI) integration is beginning to dominate investment decision-making processes for enhanced accuracy and objectivity. In the Indonesian context, startup growth is bolstered by innovative financing, though it remains hindered by regulatory factors and digital talent quality. ​